2018
DOI: 10.1093/nar/gky582
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of integration site selection upstream of tRNA genes by yeast and amoeba retrotransposons

Abstract: Transposable elements amplify in genomes as selfish DNA elements and challenge host fitness because their intrinsic integration steps during mobilization can compromise genome integrity. In gene-dense genomes, transposable elements are notably under selection to avoid insertional mutagenesis of host protein-coding genes. We describe an example of convergent evolution in the distantly related amoebozoan Dictyostelium discoideum and the yeast Saccharomyces cerevisiae, in which the D. discoideum retrotransposon D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Second, TEs have repeatedly evolved mechanisms that direct their integration into “safe” locations, where insertions will have minimal adverse effect on the organism's fitness (Boeke & Devine, ; Spaller et al , ; Cheung et al , ). These regions often consist of non‐essential repeated sequences, such as telomeric regions, ribosomal DNA arrays, upstream and downstream regions of transfer RNA genes ( tDNA s), or non‐essential regions upstream of open reading frames (Zou et al , ; Penton & Crease, ; Fujiwara et al , ; Ye et al , ; Naito et al , ; Guo & Levin, ; Pardue & DeBaryshe, ; Baller et al , ; Mularoni et al , ; Spaller et al , ; Kling et al , ). Preferential targets have been described for the integration of different classes of TEs, including retroelements (Sultana et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, TEs have repeatedly evolved mechanisms that direct their integration into “safe” locations, where insertions will have minimal adverse effect on the organism's fitness (Boeke & Devine, ; Spaller et al , ; Cheung et al , ). These regions often consist of non‐essential repeated sequences, such as telomeric regions, ribosomal DNA arrays, upstream and downstream regions of transfer RNA genes ( tDNA s), or non‐essential regions upstream of open reading frames (Zou et al , ; Penton & Crease, ; Fujiwara et al , ; Ye et al , ; Naito et al , ; Guo & Levin, ; Pardue & DeBaryshe, ; Baller et al , ; Mularoni et al , ; Spaller et al , ; Kling et al , ). Preferential targets have been described for the integration of different classes of TEs, including retroelements (Sultana et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ty1 insertion has a limiting impact on tDNA expression (Bolton & Boeke, ). Targeted integration proximal to tDNA s is a strategy that has been adopted several times by TEs to minimize damage to compact genomes (Cheung et al , ; Kling et al , ). The integration of Ty1 in these regions requires a functional Pol III promoter in the target gene (Devine & Boeke, ) and is influenced by the chromatin‐remodeling factor Isw2 and the Bdp1 subunit of TFIIIB (Bachman et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosoma brucei (66) and A. thaliana (67)). Similarly, a close genomic relationship has been demonstrated between tDNAs and retro-elements in S. cerevisiae (68)(69)(70) and with introns in Caenorhabditis species (71). In the latter, the authors showed a reduction in the expression of tRNAs residing within introns of protein coding genes effectively demonstrating a PE on the transcription of tDNAs.…”
Section: Importance Of Genomic Context On Tdna Expressionmentioning
confidence: 80%
“…Second, TEs have repeatedly evolved mechanisms that direct their integration into "safe" locations, where insertions will have minimal adverse effect on the organism's fitness Cheung et al, 2018;Spaller et al, 2016). These regions often consist of non-essential repeated sequences, such as telomeric regions, ribosomal DNA arrays, and transfer RNA genes (tDNAs), or non-essential regions upstream of open reading frames (Baller et al, 2012;Fujiwara et al, 2005;Guo and Levin, 2010;Kling et al, 2018;Mularoni et al, 2012;Naito et al, 2009;Pardue and DeBaryshe, 2011;Penton and Crease, 2004;Ye et al, 2005;Zou et al, 1996). Preferential targets have been described for the integration of different classes of TEs, including retroelements (Sultana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ty1 insertion has a limiting impact on tDNA expression (Bolton and Boeke, 2003). Targeted integration proximal to tDNAs is a strategy that has been adopted several times by TEs to minimize damage to compact genomes (Cheung et al, 2018;Kling et al, 2018). The integration of Ty1 in these regions requires a functional Pol III promoter in the target gene (Devine and Boeke, 1996) and is influenced by the chromatin-remodeling factor Isw2 and the Bdp1 subunit of TFIIIB (Bachman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%